OP59 Social Mobility Matters for Children's Well-Being – what are the Mechanisms? Findings from a UK Longitudinal Cohort Study. (10th September 2013) - Kelly, Y; Bartley, M; Sacker, A
Abstract : Background: Social mobility features high on political agendas and debates around inequalities in health but little is known about the impact of social mobility on well-being in children. Firstly, we assess whether child well-being is linked to social mobility in the first few years of life. Secondly, we examine two hypothesised mechanisms by which social mobility could influence markers of child well-being: i) via material resources - mobility is plausibly linked to changes in income and housing conditions; ii) via changes in parenting behaviours - mobility might result in changes in the home learning environment. Methods: We used data on over 9000 children from the UK Millennium Cohort Study. Social mobility was considered as change in parental occupational class (professional/managerial, intermediate, routine) in the first five years of life. Markers of child well-being were socio-emotional difficulties and performance on tests of reading, maths and spatial abilities at age 7. Results: 13.7% of families were upwardly mobile and 14.5% were downwardly mobile. There were finely graded relationships between occupational class mobility and markers of child well-being. The prevalence of clinically relevant socioemotional difficulties according to mobility categories ranged from 2.9% in children whose parents remained in the professional/managerial class for all five years to 10% in children of parents remaining in routine occupations, 5.0% of children of parents who moved from any other class to professional had difficulties, as did 8.2% of those moving from any class to routine (all p < 0.01). The equivalent mobility groups' reading scores were: stable professional 118, stable routine 106, up to professional 113, down to routine 109 (all p < 0.01). Similar patterns were observed for maths and spatial ability scores. The contribution of changes in material and parenting behavioural influences to markers of child well-being will be examined. Conclusion: Health, educational and developmental outcomes are known to be more favourable in children of more advantaged social classes, but the reasons for this are contested. Here we examine the relationships in children whose parent's social class changes during their first 5 years. Upwardly mobile children do better than those in their class of origin but not as well as their class of destination; downwardly mobile children do better than their class of destination but not as well as their class of origin. We test the extent to which this may be because social mobility is accompanied by changes in material circumstances and/or parenting behaviours that improve the home learning environment.